2017
DOI: 10.18632/oncotarget.23644
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and functional significance of Semaphorin-5A in pancreatic cancer progression and metastasis

Abstract: Semaphorin-5A (SEMA5A) has differential cell surface expression between normal and cancer cells and represents an attractive target for therapeutic intervention in pancreatic cancer (PC). In this study, we delineated the pathological expression and significance of SEMA5A during PC progression and metastasis. We utilized human tissue microarrays and different PC mouse models (Pdx1-cre; LSL- Kras(G12D), Pdx1-Cre; LSL-Kras(G12D); LSL-p53(R172H) and RIP1-Tag2) to analyze SEMA5A expression during PC progression. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…However, the role of SEMA5A in cancer has not been elucidated to date. Some researchers have found overexpression of SEMA5A in pancreatic cancer [40-44], gastric carcinoma [45-47], and prostate cancer [48], while this gene was determined to be downregulated in glioma [49, 50] and lung cancer [51]. It has also been reported that SEMA5A was coexpressed with long-chain fatty acyl-Co A synthetase 3, which predicted a better prognosis in ovarian cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of SEMA5A in cancer has not been elucidated to date. Some researchers have found overexpression of SEMA5A in pancreatic cancer [40-44], gastric carcinoma [45-47], and prostate cancer [48], while this gene was determined to be downregulated in glioma [49, 50] and lung cancer [51]. It has also been reported that SEMA5A was coexpressed with long-chain fatty acyl-Co A synthetase 3, which predicted a better prognosis in ovarian cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence suggests that axon guidance molecules such as semaphorins are involved in cancer progression, invasion, and metastasis [3]. Previous reports from our laboratory have identified one such molecule SEMA5A, which demonstrated differential expression in pancreatic tumors in comparison with the normal pancreas [5, 8].…”
Section: Discussionmentioning
confidence: 99%
“…We plated cells (5 × 10 5 ) on 22 × 22 mm sized coverslips (Fisherbrand ®, Pittsburgh, PA) placed in 6-well plates and the protocol is described previously in detail [8]. We used primary antibodies like, 1:25; E-cad, 1:5; N-cad, 1:5; β-catenin, 1:10; Fascin (Developmental Studies Hybridoma Bank) 1:20; and phalloidin (Texas Red, Molecular Probes) 1:50, and Secondary antibodies conjugated with either mouse or rabbit Cy3 (Jackson Immuno Research).…”
Section: Methodsmentioning
confidence: 99%
“…We focused our study on the poorly investigated Sema5A because, to the best of our knowledge, no data have been published yet on its expression and/or function in melanoma, but also because of its controversial role in cancer [ 9 ]. Indeed, Sema5A was found to reduce the motility of glioma cells [ 10 ], while having an opposite effect for the invasion of pancreatic, prostatic and gastric cancer cells [ 14 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%